A study in SciDB for satellite data analytics - Liu, Yikun (2016)
SciDB is an open-source array-based data management system intended primarily for use in application domains that involve very parge (petabyte) scale array data; for example, scientific applications such as astronomy, remote sensing and climate modeling. This work emphasizes on a research on the feasibility of SciDB for satellite data storage, process and query. We download, process and load Tropical Rainfall Measuring Mission (TRMM) data into the SciDB database system and the time ef- ficiency of the whole process is measured. The whole process is implemented in robust Python scripts. The implementation details are discussed and optimized. In the second part we discuss a possible data modelling for spatio-temporal operators in SciDB and show some useful operators.